2018
DOI: 10.3389/fevo.2018.00203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Strong Fixation Bias at 4-fold Degenerate Sites Across Genes in the Great Tit Genome

Abstract: It is well established that GC content varies across the genome in many species and that GC biased gene conversion, one form of meiotic recombination, is likely to contribute to this heterogeneity. Bird genomes provide an extraordinary system to study the impact of GC biased gene conversion owed to their specific genomic features. They are characterized by a high karyotype conservation with substantial heterogeneity in chromosome sizes, with up to a dozen large macrochromosomes and many smaller microchromosome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…For example, GC-biased gene conversion (described as the preferential conversion of "A" or "T" alleles to "G" or "C" during recombination induced repair) has been shown to significantly affect estimates of substitution rates, in particular at synonymous sites in birds (Galtier et al 2009;Weber et al 2014;Bolívar et al 2016;Botero-Castro et al 2017;Corcoran et al 2017;Bolívar et al 2019). However, although differences in the extent of GC-biased gene conversion across genes are known, much less is known about its variation over time, and incorporating such biases into large-scale phylogenetic frameworks is far from trivial (Gossmann et al 2018).…”
Section: The Effect Of Varying Effective Population Size and Life-history Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, GC-biased gene conversion (described as the preferential conversion of "A" or "T" alleles to "G" or "C" during recombination induced repair) has been shown to significantly affect estimates of substitution rates, in particular at synonymous sites in birds (Galtier et al 2009;Weber et al 2014;Bolívar et al 2016;Botero-Castro et al 2017;Corcoran et al 2017;Bolívar et al 2019). However, although differences in the extent of GC-biased gene conversion across genes are known, much less is known about its variation over time, and incorporating such biases into large-scale phylogenetic frameworks is far from trivial (Gossmann et al 2018).…”
Section: The Effect Of Varying Effective Population Size and Life-history Traitsmentioning
confidence: 99%
“…Owing to special features of the avian karyotype, such as a stable recombinational and mutational landscape, it seems unlikely that variation in mutation rate can contribute to the patterns observed here. However, although inter-chromosomal rearrangements are rare in birds, intra-chromosomal changes are more common and could lead to sudden changes in local mutation rates (Gossmann et al 2018). Additionally, we restricted our analysis to noncoding regions that are specific to birds or highly divergent relative to vertebrates (Seki et al 2017).…”
Section: Noncoding Regions Associated With Beak Shape Morphology Evolution Across Birdsmentioning
confidence: 99%
“…Finally, when comparing TEs to putatively neutral sites, the putatively neutral sites may not be evolving neutrally, either because of direct or linked selection. It has been shown that even synonymous sites can be under selective constraint ( Chamary and Hurst 2005 ; Chamary et al 2006 ; Eöry et al 2010 ; Künstner et al 2011 ; Gu et al 2012 ; Lawrie et al 2013 ; Gossmann et al 2018 ) and, therefore, the SFS of putatively neutral sites such as synonymous sites might be altered by natural selection. However, having weak selection affecting the putatively neutral sites might not be as important as the difference in the strength of selection between the compared sites, since the approach proposed here is evaluating frequency differences between sites of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when comparing TEs to putatively neutral sites, the putatively neutral sites may not be evolving neutrally, either because of direct or linked selection. It has been shown that even synonymous sites can be under selective constraint (Chamary and Hurst 2005; Chamary et al 2006; Eöry et al 2010; Künstner et al 2011; Gu et al 2012; Lawrie et al 2013; Gossmann et al 2018) and, therefore, the SFS of putatively neutral sites such as synonymous sites might be altered by natural selection. However, having weak selection affecting the putatively neutral sites might not be as important as the difference in the strength of selection between the compared sites, since the approach proposed here is evaluating frequency differences between sites of the same age.…”
Section: Discussionmentioning
confidence: 99%